The Maqoshid Sharia And The Importance Of Consuming Halal Food Products For Z Muslim Generation: Halal food and product - Herindar, Evania (Halal Research, 2022)
This study aims to see the effect of halal awareness and halal certification on purchasing decisions of halal food products with purchase intention as an intervening variable. In addition, this study also explains maqashid sharia on halal food products in terms of the five basic principles of maqshid sharia and their level of need. The method used in this research is path analysis by taking 151 respondents (generation Z) as the research sample drawn based on purposive sampling with a significant level of 5%. The results showed that halal awareness and halal certification positively and significantly affected buying interest. Furthermore, only halal certification and purchase intention completely and significantly affect purchasing decisions. In this study, buying interest is an intervening variable. Maqosid sharia halal food products is a shari'a goal that is ordered to consume halal food based on five main elements; hifdzud din (maintaining religion), hifdzun-nafs (guarding the soul), hifdzul-'aql (guarding reason), hifdzun nasl (keeping offspring), and hifdzul mal (maintaining the property), and considering the level of human needs, dharuriyyat (immediate needs), hajiyat (secondary needs), and tahsiniyat (tertiary needs). The implications of this research, especially for producers to carry out halal certification on their products because Z Muslim generation also aware of the importance of the halal logo when they want to buy a food product. In addition, this research is also helpful for further researchers who are interested in researching halal products by adding other variables.